Karakteristik Fisikokimia dan Sensori Stik Ampas Tahu Substitusi Tepung Mocaf dan Penambahan Bayam Hijau (Amaranthus hybridus L) - Yassinta Arnanda Ilene Putri; Yustina Wuri Wulandari; Yannie Asrie Widanti (JITIPARI, 2022)
Stick is a snacksthat haveslong, flat, savory andscrunchy taste madesfrom flour, eggs, butter, water and othersadditional seasonings. Food by-product from tofu has the potential to be used as an ingredientsfor stick makingsbecause of high protein and fiber content. In addition, local rawsmaterials such as mocaf floursand green spinach are rich in fiber content that can fulfill fiber needs of the body. This research is experimentswith purpose was to determine the physical, chemical, sensory characteristics and determine the formulation of sticks that produce high levels of fiber andsprotein. The experimental design is a completely randomized design (CRD) with the first factorscomparing tofu waste flour and mocaf flour (50: 150, 100: 100 and 150: 50) with the additionsof spinach (10%, 20% and 30%). The results showed that the stick formulation with the additionsof the best green spinach based on chemical and organoleptic values were 150 grams of tofuswaste flour, 50 grams of mocaf flour with the addition of 60 grams spinach that have a moisture content 3.742%, an ash content 2.353%, a protein 8.317 %, crude fiber 1.997%, fat 12.115% andscarbohydrate 73.473%. Based on the physical andsorganoleptic values, the tofu dregs flour was 50 grams, 150 grams of mocaf flour with the addition of 20 grams of spinach, the color yield was 2.467%, the flavor of tofu by product 2.200%, the flavor of mocaf was 2.467%, the flavor of spinach was 2.200%, the texture was crispy 3.800% and the total preference was 3.200%.s